2006
DOI: 10.1189/jlb.0106035
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that phospholipase C-dependent, calcium-independent mechanisms are required for directional migration of T lymphocytes in response to the CCR4 ligands CCL17 and CCL22

Abstract: Macrophage-derived chemokine [CC chemokine ligand 22 (CCL22)] and thymus- and activation-regulated chemokine (CCL17) mediate cellular effects, principally by binding to their receptor CC chemokine receptor 4 (CCR4) and together, constitute a multifunctional chemokine/receptor system with homeostatic and inflammatory roles within the body. This study demonstrates that CCL22 and CCL17 stimulate pertussis toxin-sensitive elevation of intracellular calcium in the CEM leukemic T cell line and human peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 77 publications
(74 reference statements)
0
39
0
Order By: Relevance
“…The latter would further enhance Erk1/2 activation. PLC␥, another ZAP-70 substrate also coupled to chemokine receptors, 51 may further contribute to Erk1/2 activation through the diacylglycerol-dependent Ras exchange factor RasGRP. 52 The early role of p52Shc in CXCR4 signaling, and the resulting impairment of ZAP-70 activation when its recruitment to p52Shc is prevented, could fully account for pleiotropic inhibitory effects of Shc1F and Shc2F on the CXCR4 cascade.…”
Section: Discussionmentioning
confidence: 99%
“…The latter would further enhance Erk1/2 activation. PLC␥, another ZAP-70 substrate also coupled to chemokine receptors, 51 may further contribute to Erk1/2 activation through the diacylglycerol-dependent Ras exchange factor RasGRP. 52 The early role of p52Shc in CXCR4 signaling, and the resulting impairment of ZAP-70 activation when its recruitment to p52Shc is prevented, could fully account for pleiotropic inhibitory effects of Shc1F and Shc2F on the CXCR4 cascade.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CCL22 increases with the progression of atherosclerosis and accumulation of macrophages, and histamine accelerates the expression of CCL22 in monocytes and leads to the differentiation of monocytes into macrophages following stimulation of the H2 receptor. This cycle of events may contribute to the onset of early atherosclerosis by recruiting monocytes and T-cells 1,29) and also promotes the progression of atherosclerosis. In fact, the apoE-KO mice had large atheromas and high levels of serum CCL22 compared with the DKO mice and apoE/H2R double-knockout mice (personal communication, by Sasaguri Y. et al from the University of Occupational and Environmental Health, Kitakyusyu, Japan).…”
Section: A B Cmentioning
confidence: 99%
“…In a subsequent study using CEM cells, both CCL17 and CCL22 were found to induce calcium flux in a PLC-dependent manner (Cronshaw et al, 2006). Calcium release was found to be dependent on inositol trisphosphate (IP 3 )-sensitive store operation.…”
Section: Ccr4mentioning
confidence: 99%